Determination of the printed documents reliability by the per-pixel comparing - ДРОНЮК, Іванна Мирославівна; НАЗАРКЕВИЧ, Марія Андріївна; ОПОТЯК, Юрій Володимирович (Ukrainian Scientific Journal of Information Security, 2013)
The paper presents a method of determining authenticity of a printed document, based on the signal-to-noise ratio criteria, which is calculated from pixel by pixel comparison of controlled and reference document images. The algorithm combines digitized documents and pixel by pixel identity checking of the appropriate document images, and processes the software tool that implements these algorithms on purpose to determine authenticity of the controlled document. Effectiveness of the software product was proved on the basis of experiments described in this paper.